Dacomitinib as a retreatment for advanced non‐small cell lung cancer patient with an uncommon EGFR mutation. Issue 8 (2nd March 2021) - Morita, Ayako; Hosokawa, Shinobu; Yamada, Kotaro; Umeno, Takahiro; Kano, Hirohisa; Kayatani, Hiroe; Shiojiri, Masaaki; Sakugawa, Makoto; Bessho, Akihiro
Abstract: In non‐small cell lung cancer (NSCLC), uncommon epidermal growth factor receptor ( EGFR ) mutations are mutations other than Ex19 deletion and Ex21 L858R, which are common mutations highly sensitive to EGFR‐tyrosine kinase inhibitors. Afatinib, a second‐generation EGFR‐tyrosine kinase inhibitor, has been shown to be effective in patients with uncommon mutations. Dacomitinib, another second‐generation EGFR‐tyrosine kinase inhibitor, has not previously been shown to be effective in patients with uncommon mutations. Here, we report the efficacy of dacomitinib for uncommon EGFR mutations in a 71‐year‐old woman diagnosed with metastatic lung adenocarcinoma with uncommon EGFR mutation (Ex18 G719A). Afatinib was administered as the first‐line treatment, and a remarkable antitumor effect was observed. However, the tumor grew after 14 months. Pemetrexed plus carboplatin followed by pemetrexed, docetaxel, atezolizumab and S‐1 were performed in sequence. Although approximately four years had passed since the start of treatment, her physical condition was good. The patient started dacomitinib as the sixth‐line treatment. Lesions were markedly reduced and treatment with dacomitinib was continued for 7.8 months. Dacomitinib is a possible treatment option for NSCLC with uncommon mutations. Abstract : Although the effectiveness of afatinib against uncommon mutations has only been reported in a combined post hoc analysis, better ORR (objective response rate) and PFS (progression‐free survival) has been shown. EGFR‐TKI re‐administration in advanced non‐small cell lung cancer (NSCLC) harboring a sensitive mutation is considered as a treatment option. Dacomitinib, another second‐generation EGFR‐TKI, was shown to be effective in patient with uncommon mutation by readministration. Dacomitinib is probably one of the treatment options for NSCLC with uncommon mutations, though more cases should be examined in the future.